Activation of CB2R with AM1241 ameliorates neurodegeneration via the Xist/miR‐133b‐3p/Pitx3 axis. Issue 9 (28th January 2020) - He, Xiaolie; Yang, Li; Huang, Ruiqi; Lin, Lijuan; Shen, Yijue; Cheng, Liming; Jin, Lingjing; Wang, Shilong; Zhu, Rongrong
Abstract: Activation of cannabinoid receptor type II (CB2R) by AM1241 has been demonstrated to protect dopaminergic neurons in Parkinson's disease (PD) animals. However, the specific mechanisms of the action of the CB2R agonist AM1241 for PD treatment have not been characterized. Wild‐type (WT), CB1R knockout (CB1‐KO), and CB2R knockout (CB2‐KO) mice were exposed to 1‐methyl‐4‐phenyl‐1, 2, 3, 6‐tetrahydropyridine (MPTP) for 1 week to obtain a PD mouse model. The therapeutic effects of AM1241 were evaluated in each group. Behavioral tests, analysis of neurotransmitters, and immunofluorescence results demonstrated that AM1241 ameliorated PD in WT animals and CB1‐KO animals. However, AM1241 did not ameliorate PD symptoms in CB2‐KO mice. RNA‐seq analysis identified the lncRNA Xist as an important regulator of the protective actions of AM1241. Specifically, AM1241 allowed WT and CB1‐KO animals treated with MPTP to maintain normal expression of Xist, which affected the expression of miR‐133b‐3p and Pitx3. In vitro, overexpression of Xist or AM1241 protected neuronal cells from death induced by 6‐hydroxydopamine and increased Pitx3 expression. The CB2 receptor agonist AM1241 alleviated PD via regulation of the Xist/miR‐133b‐3p/Pitx3 axis, and revealed a new approach for PD treatment. Abstract : The CB2 receptor agonist, AM1241, alleviated Parkinson's disease (PD) via regulation of the Xist/miR‐133b‐3p/Pitx3 axis, and revealed a new approach for PD treatment.